Studi Implementasi dan Efektivitas TPACK dalam Pembelajaran Maharah Qiro’ah - Laili Mas Ulliyah Hasan; Siti Durotun Naseha; Izzah Nur Hudzriyah Hasan (Pascasarjana Universitas Qomaruddin, 2024)
The abstract includes research objectives, methods and research results. This research aims to investigate the implementation and effectiveness of Knowledge Integration regarding Technological, Pedagogical, Content, Knowledge (TPACK) in the context of Maharah Qiro'ah learning. Qualitative research methods were used with a literature study approach. Maharah Qiro'ah material is delivered actively through the sam'iyyah-shafahiyah method using power point media. The research participants consisted of Arabic teachers who had implemented TPACK in teaching Maharah Qiro'ah at an educational institution. Data was collected through literature reviews, interviews with Arabic teachers involved in the learning process, and analysis of the learning materials used. Research findings show that implementing TPACK in Maharah Qiro'ah learning can improve the quality of teaching and learning. Teachers who have a good understanding of TPACK can integrate technology effectively in Maharah Qiro'ah teaching, thereby enriching students' learning experiences. However, challenges faced in implementing TPACK include lack of access to technology, lack of technology skills among teachers, and limited time for training. This study provides valuable insight into the importance of TPACK in the learning context of Maharah Qiro'ah and provides recommendations to support teachers in developing their TPACK skills.